1995
DOI: 10.1002/mats.1995.040040205
|View full text |Cite
|
Sign up to set email alerts
|

Persistence lengths of aromatic polyamides: a computer simulation approach

Abstract: SUMMARY:A range of polyamides has been modelled using Monte Carlo routines based on carefully determined bond-rotation potentials, bond length and bond angle. For each polymer type, a large number of chains has been built for different simulated temperatures, and the persistence lengths determined as an average over all models for a given set of conditions. The simulations predict mesogenicity of aromatic polyamides to be smaller than that of equivalent aromatic polyesters, while the experimental values of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Although TFIA with 1208 angular conformation cannot induce a crankshaft effect, its may form a cis-configuration by the ester linkage. Computer simulation shows the energy difference for ester (8 kcal/mol) is higher than the amide (2.6 kcal/mol) [30]. As a result, the ester group is conceptually more difficult to form a cis-configuration than the amide group.…”
Section: Comparison Of the Effect Of The Ortho- Meta-and Paralinkagementioning
confidence: 94%
See 1 more Smart Citation
“…Although TFIA with 1208 angular conformation cannot induce a crankshaft effect, its may form a cis-configuration by the ester linkage. Computer simulation shows the energy difference for ester (8 kcal/mol) is higher than the amide (2.6 kcal/mol) [30]. As a result, the ester group is conceptually more difficult to form a cis-configuration than the amide group.…”
Section: Comparison Of the Effect Of The Ortho- Meta-and Paralinkagementioning
confidence: 94%
“…Based on the previous computer simulation, the energy difference between the cisand trans-configuration for PhNH-COPh is very small (2.6 kcal/mol) [30] while the rotational barrier for amide group is relatively large (w16 kcal/mol) [31]. This indicates that the incorporation of cis-configuration may create a side step (crankshaft) effect between AAA and TFPA, and result in an increase in its quasi aspect ratio and local chain rigidity.…”
Section: Comparison Of the Effect Of The Ortho- Meta-and Paralinkagementioning
confidence: 95%
“…Molecular simulation shows the energy difference between trans and cis configuration for PhNH-COPh is about 2.6 kcal/ mol. 19 Compared to this energy difference, the rotational barrier of amide group is quite high and is around 16 kcal/mol, 18 which implies that the cis configuration may play a role in the conformation of the molecular chain. The cis configuration gives a 60°angular conformation, which can compensate for the 60°angular configuration induced by an ortho linkage.…”
Section: Comparison Of the Effects Of Ortho Meta And Para Linkages mentioning
confidence: 99%
“…If the critical aspect ratio is 5, the persistent length of the polymers should be longer than 55 Å at 300 °C for the polymers to exhibit liquid crystallinity. Calculation20, 21 based on a similar system indicated that the persistent length for this type of polymer is more than 60 Å at 300 °C, which meets the criteria for the polymers to exhibit liquid crystallinity despite the doubling diameter of the polymer chains. This calculation provides a solid basis for our molecular design, and it has indeed been verified by the experimental findings.…”
Section: Resultsmentioning
confidence: 74%